Expressivity as a functional property of nominative syntactic structures-MZHFI (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article the nominative syntax, as another kind of small genre forms of information and functionality osobennostі inherent specified syntactic units.
Keywords: MZHFI; nominative syntax (NS); expressiveness nominative constructions; ekspressivny MZHFI syntax